Agyu : the Ilianon epic of Mindanao. - Manuel, Esperidion Arsenio (Manila : University of Santo Tomas, 1969)
"Excerpt from Unitas vol. 42, no.2 June 1969 published by the the University of Santo Tomas"
Keywords: Epic poetry, Mindanao - -- History and criticism